Spatial and Temporal Characterization of Indoor Millimeter Wave Propagation at 24 GHz - Seok-hwan Min; Hayeon Kim; Haengseon Lee; Woo Jin Byun; Minsoo Kang; Kwangseon Kim; Bong-su Kim; Myung-sun Song (International Journal of Antennas and Propagation)
Indoor millimeter wave propagation at the frequency of 24 GHz is studied by experimental methods. Measurements are performed to obtain temporal and spatial channel model using a channel sounder and rotating antennas in a corridor. The measured impulse responses are processed to obtain compact channel model following Saleh-Valenzuela’s model. The responses are compared with those of 5.3 GHz for the same test sites. Angular spread of 24 GHz is found to be smaller than that of 5.3 GHz, while echoes of 24 GHz are found to be longer than those of 5.3 GHz.